Hunting Che : How a U.S. Special Forces Team Helped Capture the World's Most Famous Revolutionary - Weiss, Mitch and Maurer, Kevin (New York Berkley Caliber, 2013)
Based on government documents and eyewitness testimony, describes the U.S. Special Forces mission that led to the capture and execution of violent revolutionary leader Che Guevera.
Include Index, References and Epilogue
Keywords: Revolutionaries -- Special forces (Military science) -- United States